2014
DOI: 10.4236/psych.2014.51007
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Worry of River State Residents in the Niger Delta Region, Nigeria

Abstract: Human-made cataclysmic events from over 50 years of oil production, gas explosions, and oil spillages soak the Niger Delta pose psychological challenges to the people in the environment. Thus this study examined environmental worry of Rivers State residents of Niger Delta, Nigeria. Data collected were analysed using independent t-test and one-way ANOVA. The findings of the FGD revealed that there is an awareness of loss of land, loss of control of technical networks in oil production and experience of environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2016
2016
2050
2050

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
2
6
0
Order By: Relevance
“…The prevalence rates found in this study are comparable to or higher than reported in other studies in the country because our instrument was designed to measure the symptom burden in each participant’s household during the six months prior to the study; we show that the disease burden in a participant’s household is higher than that for the particular individual. As in many other previous studies [ 5 , 6 , 9 , 10 , 11 , 12 ], we found the symptoms to be correlated with the measures of exposure. The HSI score was found in this study to be significantly correlated with the distance of participant’s residence from visible oil or EEQ1 ( r = −0.213, p < 0.001); distance of participant’s residence from gas flaring facility or EEQ2 ( r = −0.60, p < 0.001); self-reported direct contact with oil pollution or EEQ3 ( r = 0.185, p < 0.001); and oil pollution in drinking water or EQ4 ( r = 0.271, p < 0.001).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The prevalence rates found in this study are comparable to or higher than reported in other studies in the country because our instrument was designed to measure the symptom burden in each participant’s household during the six months prior to the study; we show that the disease burden in a participant’s household is higher than that for the particular individual. As in many other previous studies [ 5 , 6 , 9 , 10 , 11 , 12 ], we found the symptoms to be correlated with the measures of exposure. The HSI score was found in this study to be significantly correlated with the distance of participant’s residence from visible oil or EEQ1 ( r = −0.213, p < 0.001); distance of participant’s residence from gas flaring facility or EEQ2 ( r = −0.60, p < 0.001); self-reported direct contact with oil pollution or EEQ3 ( r = 0.185, p < 0.001); and oil pollution in drinking water or EQ4 ( r = 0.271, p < 0.001).…”
Section: Discussionsupporting
confidence: 90%
“…Studies in many parts of the world suggest that living near oil spills and petroleum production sites is an environmental stressor that can have adverse effects on health, well-being, and quality of life [ 9 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. In general, oil spills/pollution can influence human health through two complementary pathways: (a) exposures to the inherently hazardous chemicals such as para-phenols and volatile benzene from the oil which can directly impair health through systemic toxicity; and (b) indirect pathways that work through the perceptions of risk, worry, annoyance, and chronic stress that moderate the sequelae of poor health outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that increased oil pollution could affect the sociodemographic and socioeconomic characteristics of the population. A negative impact on the quality of life, health, and well‐being among residents living near oil spills and petroleum production sites has been reported 15,16 . Furthermore, there is a significant difference in oil pollution exposure characteristics between women with high exposure and women with low exposure, with strong credence given to the detrimental effects of oil pollution among respondents with high exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Behavioral constraint theory premises that when human beings perceive a threat to their behavioral freedom due to spatial confinement, they are motivated to react by engaging in actions (i.e. enacting behavioral adaptation strategies) designed to reassert or maintain their behavioral freedom (Akinbobola and Njor, 2014; Andrews et al , 2015; Sommer, 2009; Stokols, 1972). Crowds are usually threatening and restricting.…”
Section: Theoretical Backgroundmentioning
confidence: 99%